Leaf Morphogenesis: Insights From the Moss Physcomitrium patens - Lin, Wenye; Wang, Ying; Coudert, Yoan; Kierzkowski, Daniel (Frontiers in Plant Science, 2021)
Specialized photosynthetic organs have independently appeared several times during the evolution of land plants. Phyllids, the leaf-like organs of bryophytes such as mosses or leafy liverworts, display a simple morphology, with a small number of cells and cell types, and lack typical vascular tissue which contrasts greatly with flowering plants. Despite this, the leaf structures in these two plant types share many common morphological characteristics. In this review, we summarize the current understanding of leaf morphogenesis in the model moss Physcomitrium patens focusing on the underlying cellular patterns and molecular regulatory mechanisms. We discuss this knowledge in an evolutionary context and identify parallels between moss and flowering plant leaf development. Finally, we propose potential research directions that may help to answer fundamental questions in plant development using moss leaves as a model system.